INVENTORY CONTROL INDIRECT MATERIAL: EOQ MODEL, EFEKTIVITAS PRODUKSI - Bachtiar, Afifi (JURNAL EKOMBIS REVIEW, 2017)
Afifi Bachtiar: Purpose of this research to know how Inventory Control Indirect Material in the form of cup size 240 ml in order to increase production effectivity at PT. Curup Aquifers. PT. Curup Aquifers has been using simple methods, while using the company's EOQ method produces cheaper cost when compared with the method that has been applied by the company. The savings generated if the EOQ method if applied to the company in 2013 amounted to Rp 76,754,449.Keywords:: Indirect Material : EOQ Model, Efektivitas Produksi